Case report: Clitoroplasty in neurofibromatosis presenting as clitoromegaly - R. Bilommi; D. Drajat (Elsevier, 2015)
Genital neurofibromatosis is a rare disorder and clitoral involvement has been reported very infrequently. Clitoromegaly is often presenting sign, in many cases it is congenital. Pathogenesis of clitoral lession due to neurofibromatosis is similar to other lession of neurofibromatosis. We present a 5 years old girl with a clitoris resembled as a phallus. The clitoral mass increase in size during the previous 4 years. This patient successfully treated by clitoroplasty, clitoroplasty was performed by preserving the glans of the clitoris and neurovascular bundles. Histopatologic examination revealed plexiform neurofibroma. To the best of our knowledge this is the first case report of clitoromegaly in neurofibromatosis in Indonesia. A complete review of literature is presented.